Non‐alcoholic fatty liver and advanced fibrosis in the elderly: Results from a community‐based Polish survey. (14th June 2017) - Hartleb, Marek; Barański, Kamil; Zejda, Jan; Chudek, Jerzy; Więcek, Andrzej
Abstract: Background & Aims: Development of non‐alcoholic fatty liver (NAFL) is dependent on metabolic factors occurring at an increased frequency with advancing age. Until now, few studies have explored the prevalence of NAFL in aged populations. Our study aimed to determine the prevalence of NAFL and advanced fibrosis in the elderly population participating in a national survey of a community‐based elderly cohort. Methods: A total of 3003 participants (mean age 79.6 years, 46.8% male) were enrolled in the study, after applying the following exclusion criteria: individuals younger than 65 years old (n=829) and those with positive serological biomarkers of HBV or HCV infection (n=391), chronic alcohol ingestion (n=727) or incomplete data records (n=745). Based on the fatty liver index (FLI), the participants were classified into three categories: FLI<30 (no NAFL), 30≤FLI<60 (borderline) and FLI≥60 (NAFL). According to the non‐alcoholic fatty liver disease (NAFLD) fibrosis score (NFS), the participants were divided into three advanced fibrosis risk categories: NFS<−1.455 (low risk), −1.455≤NFS≤0.676 (intermediate risk) and NFS>0.676 (high risk). Results: The prevalence of NAFL in the general population was 37.2%; the prevalence reached 51.4% in participants 65‐70 years of age and decreased with advancing age ( P <.0001). The prevalence of advanced fibrosis was 7.79% (14.8% in the NAFL population) and increased with advancing age ( P <.005). Conclusions: The prevalence of NAFL and metabolically driven advanced fibrosis are relatively common in the elderly population, and these hepatic conditions run in adverse directions with advancing age.